A Study on the Teaching System to Promote Learning by Competition–A Case Study of the Business School of Lingnan Normal University - Yan, Miaoru; Shia, An-Shin; Badiane, Kemo (Advances in Social Sciences Research Journal, 2022)
The cultivation of high-quality talents with applied innovation is the fundamental task of undergraduate teaching in colleges and universities. Disciplinary competitions play a significant role in promoting and practicing in the cultivation of undergraduate students (Zhu P, 2020). Based on the analysis of the current situation of discipline competition and teaching in the Business School of Lingnan Normal University, this paper investigates the enthusiasm of business school students to participate in discipline competition in the form of a questionnaire and puts forward the problem of disconnection between theoretical and practical teaching at this stage. The data analysis of the results of the questionnaire survey and the review of relevant materials put forward solutions to various problems and provide a reference for the integration of practice and theoretical teaching of local college subject competitions.